2014
DOI: 10.1186/1471-2458-14-1022
|View full text |Cite
|
Sign up to set email alerts
|

Association between mobile phone use and inattention in 7102 Chinese adolescents: a population-based cross-sectional study

Abstract: BackgroundThe dramatic growth of mobile phone (MP) use among young people has increased interest in its possible health hazards in this age group. The aim of this cross-sectional study was to investigate the association between MP use and inattention in adolescents.MethodsA total of 7720 middle school students were involved in this cross-sectional study. Inattention was assessed as defined for the Attention Deficit component of Attention deficit/Hyperactivity disorder (ADHD) by the Diagnostic and Statistical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 39 publications
3
54
0
10
Order By: Relevance
“…The cross-sectional associations for self-reported duration of gaming and data traffic on the mobile phone are in line with the findings of Byun et al (2013) and Zheng et al (2014) of ADHD symptoms being related to mobile phone use for gaming (Byun et al 2013) and of inattention to time spent on the mobile phone for entertainment (Zheng et al 2014). For these cross-sectional analyses reverse causality is of concern.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The cross-sectional associations for self-reported duration of gaming and data traffic on the mobile phone are in line with the findings of Byun et al (2013) and Zheng et al (2014) of ADHD symptoms being related to mobile phone use for gaming (Byun et al 2013) and of inattention to time spent on the mobile phone for entertainment (Zheng et al 2014). For these cross-sectional analyses reverse causality is of concern.…”
Section: Discussionsupporting
confidence: 83%
“…Korean children (Byun et al 2013) or inattention in 7,102 Chinese adolescents (Zheng et al 2014). But interestingly, they found mobile phone use for playing games (Byun et al 2013) and the time spent on the mobile phone for entertainment (Zheng et al 2014) being associated with ADHD symptoms and inattention, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found hyperactivity and ADHD associated with problematic internet use (Kaess et al 2014;Ko et al 2012;Kormas et al 2011;Ozturk et al 2013) and using the mobile phone for entertainment (playing games, internet) (Byun et al 2013b;Zheng et al 2014). Hyperactive adolescents are easily distracted, show problems in sustaining attention and are less capable of impulse control (Douglas 1972).…”
Section: Behaviour and Problematic Mobile Phone Usementioning
confidence: 99%